Extraskeletal Chondroma: Another Diagnostic Possibility for a Soft Tissue Axillary Mass in an Adolescent. (27th December 2011) - Adaletli, Ibrahim; Laor, Tal; Yin, Hong; Podberesky, Daniel J.
Abstract : Extraskeletal chondroma is a benign cartilaginous tumor that occurs predominantly in the soft tissues near small joints of the hands and feet. There are rare reports of the lesion in other sites, such as the head, neck, trunk, oral cavity, larynx, and pharynx. We present a case of an axillary mass in a 15-year-old girl who underwent MRI examination and resection, with the ultimate diagnosis of an extraskeletal chondroma, in order to expand the differential diagnosis of an axillary soft tissue mass in an adolescent.